2014
DOI: 10.5194/tc-8-623-2014
|View full text |Cite
|
Sign up to set email alerts
|

Surge dynamics in the Nathorstbreen glacier system, Svalbard

Abstract: Abstract. Nathorstbreen glacier system (NGS) recently experienced the largest surge in Svalbard since 1936, and this was examined using spatial and temporal observations from DEM differencing, time series of surface velocities from satellite synthetic aperture radar (SAR) and other sources. The upper basins with maximum accumulation during quiescence corresponded to regions of initial lowering. Initial speed-up exceeded quiescent velocities by a factor of several tens. This suggests that polythermal glacier su… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
60
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 63 publications
(86 reference statements)
2
60
0
Order By: Relevance
“…The comparison of Figure 9a,b also nicely shows the end of the surge of the Nathorstbreen glacier system, which started in 2009 with a frontal advance of about 15 km [17]. In order to further characterize the spatio-temporal dynamic pattern of this glacier system we compare in Figure 11a For many other glaciers over the Svalbard Archipelgo a steady increase of frontal velocities along with a retreat of frontal positions is observed.…”
Section: Variability Of Glacier Dynamics Over Svalbardmentioning
confidence: 80%
See 1 more Smart Citation
“…The comparison of Figure 9a,b also nicely shows the end of the surge of the Nathorstbreen glacier system, which started in 2009 with a frontal advance of about 15 km [17]. In order to further characterize the spatio-temporal dynamic pattern of this glacier system we compare in Figure 11a For many other glaciers over the Svalbard Archipelgo a steady increase of frontal velocities along with a retreat of frontal positions is observed.…”
Section: Variability Of Glacier Dynamics Over Svalbardmentioning
confidence: 80%
“…This region was also investigated by [8] with a focus on mass budgets (both surface and calving) for the 1991-2015 period. Similarly, Melkonian, A. et al [14] investigated velocities and elevation changes for Novaya Zemlya (Russian Arctic) and numerous studies have analysed the changes in Svalbard (e.g., [5,15,16]) with a special focus on surge-type (e.g., [17][18][19]) or continuously fast-flowing (e.g., [20]) glaciers. However, there are no comprehensive recent studies on flow velocities for GIC on Franz Josef Land and Severnaja Zemlya, only older ones [21,22] or short communications on rapid glaciers changes [23].…”
Section: Introductionmentioning
confidence: 99%
“…The overall ice flux to the ocean from all 163 Svalbard glaciers was estimated to be 6.75 ± 1.7 Gt a −1 (Blaszczyk et al, 2009), and Kronebreen and Kongsbreen are major contributors with shares of 4.0 and 2.5 %, respectively. Nevertheless, this number does not include mass loss related to major surges, such as of Basin-3 on Austfonna since 2012 (4.2 ± 1.6 Gt a −1 , Dunse et al, 2015) and between 2009 and 2013 of Nathorstbreen (Sund et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In 2009, Dobrowolskibreen started to surge, and in 2010 the whole Nathorstbreen system consisting of Nathorstbreen (N), Dobrowolskibreen (D), Polakbreen (P) and Zawatzkibreen (Z) followed [20]. Sund et al [20] found maximum velocities of 25 m·d −1 during the initiation of the Nathorstbreen glacier system surge. Three years later, the glacier still flows at an accelerated rate with a maximum velocity of about 3 m·d −1 .…”
Section: Discussionmentioning
confidence: 99%
“…Glacier surface velocity is known for many glaciers on Svalbard (e.g., [12][13][14][15][16][17][18][19][20][21]), but none of these studies provide an overview of velocities across the entire archipelago. The first goal of this study is therefore to provide the first complete surface velocity map for all glaciers on Svalbard.…”
Section: Introductionmentioning
confidence: 99%